Sex and gender determinants following spinal fusion surgery: A systematic review of clinical data - Salamanna, Francesca; Contartese, Deyanira; Tschon, Matilde; Borsari, Veronica; Griffoni, Cristiana; Gasbarrini, Alessandro; Fini, Milena (Frontiers in Surgery, 2022)
In the last decade numerous studies analyzed and described the surgical outcomes in male and female patients submitted to orthopedic surgery. Although this, the impact of sex/gender on spinal fusion surgery clinical outcomes is still poorly defined. This review systematically maps and synthesizes the scientific literature on sex/gender differences in postoperative outcomes for patients undergoing to spinal fusion surgery. Search was performed in PubMed, Scopus, and Web of Science in the last 22 years. Clinical studies evaluating potential sex/gender differences in post-operative outcomes and/or complications, as primary or secondary aim, were included and analyzed. Out of the 1885 records screened, 47 studies were included. These studies comprised a total of 1.158.555 patients (51.31% female; 48.69% male). About 77% of the analyzed studies reported sex/gender related differences in post-operative outcomes. Most studies treated patients for lumbar degenerative diseases and more than 55% of them reported a worse post-operative outcome in female patients in term of pain, disability, Health-Related Quality of Life questionnaires and complications. Differently, a significant heterogeneity across studies on patient treated for cervical and sacral degenerative diseases as well as for spinal deformity and traumatic spinal fracture, prevented the understanding of the specific sex/gender differences after spinal fusion surgery. Despite this the present review highlighted that females’ patients treated for lumbar degenerative spine diseases could require more clinical awareness during postoperative care. The understanding on how sex/gender differences can really affect clinical outcomes after spinal fusion surgeries is mandatory for all spinal pathological condition to drive clinical research towards oriented and personalized protocols.